Nabokov's Amphiphorical Gestures - S. E. Sweeney (Studies in 20th & 21st Century Literature, 1987)
In addition to using two primary kinds of metaphors (those that clarify descriptions, and those that develop into leitmotifs), Nabokov's fiction demonstrates a third kind that is characterized by extended analogies, baroque, seemingly uncontrolled imagery and rhetoric, and, most importantly, fundamental ambiguity. Although this inherent ambiguity is developed throughout the comparison, it is never resolved. Because of this distinguishing characteristic, I have named such metaphors "amphiphors," after one of Nabokov's own neologisms. Nabokov's comments in Nikolai Gogol and Lectures on Russian Literature, as well as direct allusions to Gogol embedded in a few amphiphors, suggest that this device evolved directly from Gogol's absurd, overgrown images and Protean minor characterizations. Yet, whereas Gogol's "spontaneous generation" is careless, uncontrolled, and comical, Nabokov uses his amphiphors deliberately for ironic effect. More precisely, he exploits the gap between the initial and final points of the comparison to create a sustained and irreconcilable ambiguity—what William Empson called the seventh type, "at once an indecision and a structure." Moreover, close textual analysis of the mechanics of several amphiphors, from Speak, Memory and Bend Sinister, shows marked similarities in content and authorial intention. In each instance, Nabokov uses the amphiphor's inherent stylistic ambiguity to delineate a similar phenomenological one: his own ambivalence towards death (whether his own, his father's, or his hero's) and the insolubility of its "monstrous riddle."
Keywords: Nabokov; metaphor; leitmotif; fiction; intended analogy; analogy; baroque; imagery; rhetoric; ambiguity; amphiphor; neologism; Nikolai Gogol; Lectures on Russian Literature; Gogol; Speak Memory; Bend Sinister; death